Effects of Bi doping on structural and magnetic properties of cobalt ferrite perovskite oxide LaCo0.5Fe0.5O3. Issue 11 (1st June 2022) - Haque, Ariful; Bhattacharya, Sudipa; Das, Radhamadhab; Hossain, Akbar; Gayen, Arup; Kundu, Asish K.; Vasundhara, M.; Seikh, Md. Motin
Abstract : Literature reports on magnetic transition of LaFe0 . 5 Co0 . 5 O3 are highly ambiguous. The present study is an endeavour to address that particular issue of this ferrite perovskite. Here we report the low temperature sol-gel synthesis of pure and Bi-doped La1-x Bix Fe0 . 5 Co0 . 5 O3 (x = 0, 0.1 & 0.2) perovskites. All the samples were characterized by powder X-ray diffraction, X-ray photoelectron spectroscopy, field emission scanning electron microscopy, energy dispersive X-ray (EDX) analysis and magnetization studies. LaFe0 . 5 Co0 . 5 O3 crystallizes in a single phase rhombohedral (R -3c ) structure. Substitution of Bi at the A-site results in structural transition. La0.9 Bi0.1 Fe0 . 5 Co0 . 5 O3 exhibits mixed rhombohedra (R -3c ) and orthorhombic (P bnm ) phases, whereas La0.8 Bi0.2 Fe0 . 5 Co0 . 5 O3 is single phase orthorhombic (P bnm ). Favourable grain growth and good crystallinity observed in Bi doped samples are possibly due to the low melting temperature of Bi containing La1-x Bix Fe0.5 Co0.5 O3 . EDX analysis confirms the chemical homogeneity of the samples. XPS studies and bond valence sum calculations confirm the nominal cationic oxidation states of the ions. Magnetization measurements reveal the weak ferromagnetic nature of La1-x Bix Fe0 . 5 Co0 . 5 O3 (x = 0, 0.1 & 0.2) which is associated to the canted antiferromagnetic structure. The magnetically active subsystem of Fe 3+ ions are responsible for weak ferromagnetism which is explained by the antisymmetric Dzyaloshinskii–Moriya interaction, whereas the Co 3+ ions remain predominantly in the low spin state. The increase in magnetic transition and the lower magnetic moment with an increase in Bi content can be related to the weakening of Dzyaloshinskii–Moriya interaction due to structural modification and local lattice distortion associated to the stereochemically active 6s 2 lone pair electrons of the Bi 3+ ions. Our results confirm the high structure sensitivity of magnetic properties of cobalt ferrite perovskite.